Embodiment of the Concept of Time in William Faulkner’s “As I Lay Dying” and Virginia Woolf’s “To the Lighthouse” - Ulvydienė, Loreta; Buivytė, Giedrė (Respectus Philologicus, 2013)
This article applies the theory of cognitive semantics as a framework for interpreting the embodiment of the concept of time in two modernist novels written using the stream-ofconsciousness technique: William Faulkner’s As I Lay Dying (1930) and Virginia Woolf’s To the Lighthouse (1927). Metaphorical projections of time are investigated as: being based on image schemas, structuring bodily experience, and cross-domain conceptual mappings. The motion of time in accordance with the life events and mental states of the characters is analysed as a reflection of cognitive structures containing the concept of time or referring to it metaphorically. We claim that time in To the Lighthouse is conceptualised by elaborating concepts of distance, space and water, while in As I Lay Dying time is conceptualised in a bidirectional in–out relation with the human body, as a destructive force and as spatial distance. Moreover, as the space of time proposes a model of a continuum in which a certain space may be active only in a certain moment of time, the important notion of being beyond time is discussed. Ultimately, the conclusion is drawn that the conceptualisation of time as distance, noticed in To the Lighthouse, is also found in As I Lay Dying. Both Woolf and Faulkner respond to elusive and obscure modern temporality and succeed in creating links between the past and the present.